Granulomatous Liver Disease in Ataxia-Telangiectasia With the Hyper-IgM Phenotype: A Case Report - Szczawińska-Popłonyk, Aleksandra; Ossowska, Lidia; Jończyk-Potoczna, Katarzyna (Frontiers in Pediatrics, 2020)
Ataxia-telangiectasia (A-T) is an autosomal recessive disorder characterized by neurodegeneration, combined immunodeficiency, and oculocutaneous telangiectasia. The hyper-IgM phenotype of A-T, correlating with a class-switch recombination defect, IgG and IgA deficiency, T helper and B cell lymphopenia, immune dysregulation, proinflammatory immune response, autoimmune disease, and a high risk of lymphomagenesis. Progressive liver disease is a hallmark of classical A-T with the hyperIgM phenotype and manifests as non-alcoholic hepatic steatosis and fibrosis. We report a case of an 17-year-old male A-T patient, in whom a progressive granulomatous liver disease with portal hypertension, has led to massive splenomegaly and hypersplenism, metabolic liver insufficiency, bleeding from esophageal varices and pancytopenia. In this patient an unusual severe disease course with a highly variable constellation of A-T symptomatology includes granulomatous skin, visceral, and internal organs disease with liver involvement.The liver disease is associated with the hyper-IgM immunophenotype and escalating neurodegeneration, creating a vicious circle of immune deficiency, permanent systemic inflammatory response, and organ-specific immunopathology.